Effects of offering incentives for reviews on trust: Role of review quality and incentive source. (January 2022) - Ai, Jin; Gursoy, Dogan; Liu, Yue; Lv, Xingyang
Abstract: Incentives are often used by businesses to motivate customers to post reviews of their products or services online. However, the impact of those incentives on customers who are on the receiving end of such electronic word-of-mouth (eWOM) behaviors are rarely examined. This study explores the effects of incentive-driven eWOM on receivers' trust (customer trust) utilizing norm conflict and stakeholder perspectives. The findings indicate that customers have less trust in incentive-driven eWOM than in organic eWOM, for two reasons. First, the sharing of eWOM follows social norms, whereas incentives fall under market norms. This creates a potential conflict of norms for the receivers of incentivized eWOM. Second, the offer and acceptance of incentives establish interest relevance between businesses and posters. The findings suggest that increasing the quality of eWOM and hiding interest relevance between posters and businesses by changing the incentive source can alleviate the conflict of norms and increase customer trust in those reviews. This study provides a theoretical basis and suggests practical strategies for businesses to actively manage their customers' incentive-based eWOM behavior. Highlights: Receivers consider the incentive-motivated eWOM less trustworthy compared with organic eWOM. Increases in eWOM quality can decrease the perceived norm conflict and increase receivers' trust. Source of the incentive source can influence receivers' trust. Source of the incentive source can influence the perceived interest relationship between the sender and the business.